2022
DOI: 10.1002/ldr.4174
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter and geochemical characteristics shape microbial community composition and structure across different land uses in an Australian wet tropical catchment

Abstract: Soil characteristics vary across land uses, and soil microbial communities are likely to respond to such variations. However, such responses are not well understood. In this study, we examined how specific changes in soil organic matter (SOM) and geochemical characteristics influenced the bacterial and fungal community composition and structure across land uses. Soil samples were collected from grazing, sugarcane, forest and banana land uses in the Johnstone River catchment (wet tropics), northeastern Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Maize soil had the highest content of OM (Figure 1a and Table S3), which might be due to the following aspects: (1) Plant types of roots, root exudates, plant residues, and litter in the soil. The soil organic matter is introduced mainly due to the decomposition of roots, root exudates, litter, and plant residues in the soil (Bahadori et al, 2022; Schmidt et al, 2011). Although maize (C 4 ) has greater carbon sequestration capacity than cabbage and cocozelle (C 3 ) (Vadez et al, 2021), maize litter and plant residues contain more carbon.…”
Section: Discussionmentioning
confidence: 99%
“…Maize soil had the highest content of OM (Figure 1a and Table S3), which might be due to the following aspects: (1) Plant types of roots, root exudates, plant residues, and litter in the soil. The soil organic matter is introduced mainly due to the decomposition of roots, root exudates, litter, and plant residues in the soil (Bahadori et al, 2022; Schmidt et al, 2011). Although maize (C 4 ) has greater carbon sequestration capacity than cabbage and cocozelle (C 3 ) (Vadez et al, 2021), maize litter and plant residues contain more carbon.…”
Section: Discussionmentioning
confidence: 99%
“…4a ). The biological component of SPM represented by microbial diversity and community structure (MDCS), consisting of bacterial and fungal richness (BactRich and FunRich), diversity (Shannon Index - BactShann and FunShann) and community structure (BactNMDS and FunNMDS) 33 , 34 . Our results showed that the shift in MDCS was highly correlated with the variation in environmental factors (Env2) and organic carbon characteristics (OCC) of the SPM across habitat types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The main differences among the three (bio) organic fertilizers were that NBW was inoculated with B. subtilis , and HLJ organic fertilizer had a higher organic matter content than CM. According to a previous report, SOM characteristics were the major drivers of soil microbial community structure, while soil bacterial communities were more sensitive to variations in SOM content than fungal communities (Bahadori et al., 2022). The variance partitioning analysis (VPA) suggest that microbial biological factors mainly promoted the transformation of P forms.…”
Section: Discussionmentioning
confidence: 98%